The changing face of abuse cases in a pediatric intensive care unit: A single-center experience - ALTAŞ, ZEYNEP MEVA (My University, 2022)
Background: Due to the increase in abuse and neglect cases in recent years, the purpose of this study was to assess child abuse and neglect of patients who were hospitalized and followed up in our pediatric intensive care unit (PICU). Methods: A total of 34 abuse and neglect patients who were admitted to the PICU from August 2020 to March 2021 were included retrospectively in the study. Patients’ clinical and demographic characteristics were obtained from our hospital’s patient record system (HIS). Comorbidities and the mental status of the patients, affected systems, treatments, and outcomes were extracted. Results: In this study, 44.1% (n: 15) of the patients were male and 55.9% (n: 19) were female. Physical neglect such as foreign body aspiration, malnutrition, electrocution, drowning, traffic accident, and body collision was detected in 14 (41.2%) patients. Emotional neglect (taking drugs, alcohol, or suicide) was found in 19 (55.9%) of our patients. Only 1 (2.9%) patient presented with physical abuse. Conclusions: Perception of neglect varies among different cultures. Any infant or child who is admitted to the PICU with a history that is not consistent, a history of delay in seeking medical attention, a previous history of abuse or suspected abuse, or the absence of the primary caretaker at the appearance of illness should signal possible abuse. Health-care professionals should give more attention to these patients to prevent the overlooking and recurrence of neglect and abuse cases due to the intense work tempo in the PICU.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; child abuse; emotional neglect; pediatric intensive care unit; physical neglect; CHILD-ABUSE; HEAD-INJURY; FRACTURES; child abuse; emotional neglect; pediatric intensive care unit; physical neglect.